The Italian Corte di Cassazione rules on the Recognition in Italy of a Foreign Judgment on the Merits preceded by the issuance of a Freezing Order: Reflections on the Ruling of 16 September 2021 No. 25064 - Monico, Rebekka (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
With its decision No. 25064/2021 the Italian Corte di Cassazione ruled on the compatibility with Italian procedural public policy (and, therefore, on the recognition) pursuant to Art. 64, letter g, of Law 218/1995 of a foreign judgment preceded by the issuance of a worldwide Mareva (nowadays freezing) order rendered within the same proceeding. The Court’s ruling offers the opportunity to make some considerations on the circulation of worldwide Mareva injunctions within the European judicial space and on the instrument of adaptation under Art. 54 of Regulation 1215/2012. These issues remain topical even after Brexit given the continuing power of the courts of some EU Member States to issue freezing injunctions.